Using Flashcards to Improve Students’ Vocabulary Mastery in SD Hafizh Al-Qurbah Parepare - Pratiwi Samad (LETS: Journal of Linguistics and English Teaching Studies, 2022)
Vocabulary mastery is a basic for language skill development especially in learning a foreign language. This research aims to improve learning outcomes in vocabulary teaching through flash cards. The study was conducted from 08 to 17 October 2019 at SD Hafizh Al-Qurbah Parepare with 15 students as respondents. This study uses a classroom action research method consisting of II cycles with stages in each cycle including planning, implementation, observation and reflection. To obtain the data, the researcher implemented the test and observational sheet as the instrument. The result shows that there is a significant improvement shown from the students’ score achieves 76 in cycle I then increase to 83 in cycle II and the students’ activity improves from the observational sheet description.